“I Can be Who I Am When I Play Tekken 7”: E-sports Women Participants from the Islamic Republic of Pakistan - Hussain, Umer; Yu, Bo; Cunningham, George B.; Bennett, Gregg (Games and Culture, 2021)
Extant research on e-sports has focused on the growth and value of the phenomenon, fandom, and participant experiences. However, there is a paucity of e-sports scholarship detailing women’s experiences from marginalized communities living in various conservative Muslim countries. This shortage of literature remains despite different radical Islamic groups’ consistent demand for banning several online video games and the Muslim youth’s resistance to these calls. This study aimed to understand the motives and lived experiences of Muslim women e-sports participants from Gilgit-Baltistan, Pakistan. The authors collected data via observations of online video games and in-depth interviews. The study participants revealed that they use e-sports as a vehicle for an oppositional agency and personal freedom from the patriarchal system. The findings also suggest that participants are facing systematic marginalization and grave intrusion of post-colonization. The study contributes to the limited scholarship concerning Indian subcontinent Muslim women’s e-sports participation.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digital Middle East: State and Society in the Information Age - Zayani, Mohamed (Oxford University Press, 2018)
In recent years, the Middle East’s information and communications landscape has changed dramatically. Increasingly, states, businesses, and citizens are capitalizing on the opportunities offered by new information technologies, the fast pace of digital transformations, and enhanced connectivity. These changes are far from turning Middle Eastern nations into network societies, but their impact is significant. The growing adoption of a wide variety of information technologies and new media platforms in everyday life has given rise to complex dynamics that beg for a better understanding. Digital Middle East sheds a critical light on continuing changes that are closely intertwined with the adoption of information and communication technologies in the MENA region. Drawing on case studies from throughout the Middle East, the contributors explore how these digital transformations are playing out in the social, cultural, political, and economic spheres, exposing the various disjunctions and discordances that have marked the advent of the digital Middle East.
Keywords: 1-Jeux vidéo; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé

Les Jeux Video en Negroculture: Contribution a Une Anthropologie de La Solidarite Chez Les Jeunes du Cameroun - Otye Elom, Paul Ulrich (African Sociological Review / Revue Africaine de Sociologie, 2015)
En Afrique en général et au Cameroun en particulier, posséder une console de jeux vidéo n’est pas à la portée de tout le monde. Les jeunes puisque ce sont eux qui les affectionnent particulièrement, qui en possèdent une, font donc souvent appel à leurs pairs afin qu’ensemble, ils puissent s’amuser. L’espace où les jeunes jouent aux jeux vidéo devient de ce fait un espace où ces derniers s’affirment en tant que groupe à part entière. C’est un espace qui leur permet de se démarquer des adultes qui, le plus souvent dénigrent, voire méprisent cette activité ludique. Les jeunes y créent ainsi des « ethnométhodes » et développent une solidarité mécanique. Jouer aux jeux vidéo dans ce contexte n’est plus simplement une activité de loisir. L’espace de jeu devient un espace où se créent de nouvelles relations et où se raffermissent les anciennes. Mais également, un espace où se développent l ’esprit de compétition et corrélativement même des conflits. Celui avec qui on s’amuse aux jeux vidéo devient celui à qui on se confie, avec qui on partage ses joies et ses peines. La console de jeux n’ « appartient » plus à celui qui l ’a achetée, mais à tous ceux qui la jouent. Il n’est donc pas rare qu’elle s’exporte du domicile de son propriétaire pour le domicile d ’un autre adolescent. Il faut également préciser que le jeu vidéo reste en négroculture une activité essentiellement masculine ; l ’espace de jeu est donc le fief du garçon et les filles n’ont rien à y faire. Le jeu vidéo développe ainsi un certain machisme, une fierté d ’être homme plutôt que femme. Dans ce contexte, on peut noter une sorte de détribalisation. L’obédience ethnique de tout un chacun s’estompe pour laisser place à une société des jeunes tout court. Le jeu vidéo fait donc tomber les barrières raciales, tribales, ethniques. Et même si on peut y noter des effets pervers, ce qui est normal, puisque aucun système culturel n’est parfait, les jeux vidéo en contexte camerounais développent chez les adolescents le sentiment d ’appartenance à une même classe d ’âge.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé